Manual of Clinical Dialysis - Ahmad, Suhail (Springer US : Imprint: Springer, 2009)
This second edition of the Manual of Clinical Dialysis is a concise and well-illustrated guide to all aspects of dialysis. All chapters have been revised and present a complete overview of the techniques, processes and equipment involved in clinical dialysis as well as an overview of the complications of dialysis. The manual also provides an overview of common clinical problems related to renal failure such as hypertension, anemia and renal osteodystrophy. Suhail Ahmad, M.D., is Professor of Medicine and Medical Director, Dialysis/Apheresis/Hypertension, University of Washington; Medical Director, Scribner Kidney Center; and Senior Medical Director, Northwest Kidney Centers, Seattle, Washington.